Pengendalian Risiko Tumpahan Minyak pada Operasi Kapal di Perairan Terbatas Berbasis OSERRAT dan Analisis SWOT - Ipan Juanda; Ninin Gusdini; Lie, Ling Piao Alvin (CV. Ulil Albab Corp, 2026)
Oil spills in restricted waters such as ports and offshore operational areas represent high-consequence environmental risks due to dense vessel traffic, the sensitivity of coastal ecosystems, and their proximity to socio-economic activities. This study aims to evaluate the operational risk level of oil spills and assess shipboard emergency response preparedness using the Hazard Identification, Risk Assessment and Determining Control (HIRADC) approach and the Oil Spill Emergency Response Readiness Assessment Tool (OSERRAT). Furthermore, the analytical results are integrated into a SWOT matrix to formulate evidence-based risk control strategies. The study was conducted on five operational vessels of PT X during the second semester of 2025 using a descriptive-qualitative approach supported by quantitative scoring. The HIRADC analysis indicates that bunkering and berthing/unberthing operations present high-risk levels. OSERRAT preparedness scores range from 22.89% to 51.11%, indicating inadequate readiness relative to the identified risk levels. SWOT analysis positions the organization in the Weakness Opportunity quadrant (IFE 3.30; EFE 3.65), suggesting that priority strategies should focus on strengthening internal capacity by leveraging regulatory and technological opportunities. This study proposes an integrative oil spill risk control model based on preparedness evaluation and strategic management, offering practical applicability for national shipping companies in supporting sustainable environmental governance.